2011
DOI: 10.1159/000292644
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Role of Pathology in Breast Cancer Diagnosis and Treatment

Abstract: Pathological examination has been the gold standard for diagnosis in cancer and its role has also included the elucidation of etiology, pathogenesis, clinicopathological correlation, and prognostication. The advent of newer technologies and the realization that breast cancer is heterogeneous has shifted the focus to prognostication, with increased attention being paid to the identification of morphological features and immunohistochemical markers of prognostic relevance. However, despite the massive efforts in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(79 citation statements)
references
References 297 publications
(168 reference statements)
0
75
0
4
Order By: Relevance
“…4,21,32 Previous studies focusing on the molecular expression of ERα and PR in HBC have shown the behavior of the 2 molecules to be very similar, possibly because PR expression is strongly dependent on ERα. 14,19,25 In addition, immunohistochemical (IHC) staining for PR is less consistent compared to ERα. 18 In the current study, ERα was used as an indicator for HR expression.…”
Section: Introductionmentioning
confidence: 99%
“…4,21,32 Previous studies focusing on the molecular expression of ERα and PR in HBC have shown the behavior of the 2 molecules to be very similar, possibly because PR expression is strongly dependent on ERα. 14,19,25 In addition, immunohistochemical (IHC) staining for PR is less consistent compared to ERα. 18 In the current study, ERα was used as an indicator for HR expression.…”
Section: Introductionmentioning
confidence: 99%
“…8 Indikasi pemeriksaan potong beku adalah untuk menetapkan diagnosis dari lesi payudara sebelum dilakukan terapi defenitif serta untuk mengevaluasi margin reseksi. 8 4 Secara tradisional, patolog melalukan pemeriksaan makroskopik dan mikroskopik dari spesimen eksisi yang diterima. Secara makroskopik penilaian dilakukan terhadap integritas spesimen, ukuran spesimen, ukuran tumor, focalitas tumor, perluasan tumor secara makroskopik, dan jumlah kelenjar limfe yang diperiksa.…”
Section: Ii2 Diagnosis Patologi Intraoperatifunclassified
“…Hal ini juga membuka peranan baru patologi dalam prognostik dan tatalaksana kanker payudara. 4 Daftar Pustaka…”
Section: Penutupunclassified
“…In this ever-changing era in the diagnosis and treatment of breast cancer, pathologists, the keepers and purveyors of excised tissues, have extended their role by employing new technologies to examine the molecular complexities of breast cancer relating thus its biological heterogeneity to prognosis and treatment, and issuing recommendations aiming to improve the handling and reporting of the specimens [20]. With this paper we aspire to contribute positively to this global effort of post-NAST breast cancer specimens reporting standardization by looking into the Spanish reality of daily practice of accurately defining pCR.…”
Section: Introductionmentioning
confidence: 99%